WUE estimation by using direct and indirect modelling of water losses of sugar beet cropped in a semi-arid environment - Ferrara R.M.; Introna M.; Martinelli N.; Rana G. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
Many expressions of water use efficiency (WUE) have been proposed in literature, but the most diffuse one is based on the ratio between crop yield and cumulative actual evapotranspiration (ETa). A big error can be made if the water consuming is badly evaluated. The best way to give the ETa is to measure it, but often it is estimated. At plot scale, there are two different methods for estimating ETa: the direct and the indirect method, both based on the Penman-Monteith model. In order to evaluate the errors made on WUE due to the ETa modelling, in this work we evaluate the water use efficiencies in the growth period when LAI is greater or equal to 2. Three methods of ETa estimation is used (direct, single Kc, dual Kc) for a sugar beet crop cultivated in Capitanata Plain (southern Italy) during two experimental field campaigns. The actual evapotranspiration has been measured directly by eddy covariance or by aerodynamic method. All the measurements have been done at hourly scale, but the estimation are presented at daily and seasonal scales. The results show that for WUE indicators, the direct method of ETa calculation gave better performances with respect to the indirect ones, with worst results for the single crop coefficient approach.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)